-3(x+8)-2(4x-3)=-7

Simple and best practice solution for -3(x+8)-2(4x-3)=-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(x+8)-2(4x-3)=-7 equation:


Simplifying
-3(x + 8) + -2(4x + -3) = -7

Reorder the terms:
-3(8 + x) + -2(4x + -3) = -7
(8 * -3 + x * -3) + -2(4x + -3) = -7
(-24 + -3x) + -2(4x + -3) = -7

Reorder the terms:
-24 + -3x + -2(-3 + 4x) = -7
-24 + -3x + (-3 * -2 + 4x * -2) = -7
-24 + -3x + (6 + -8x) = -7

Reorder the terms:
-24 + 6 + -3x + -8x = -7

Combine like terms: -24 + 6 = -18
-18 + -3x + -8x = -7

Combine like terms: -3x + -8x = -11x
-18 + -11x = -7

Solving
-18 + -11x = -7

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '18' to each side of the equation.
-18 + 18 + -11x = -7 + 18

Combine like terms: -18 + 18 = 0
0 + -11x = -7 + 18
-11x = -7 + 18

Combine like terms: -7 + 18 = 11
-11x = 11

Divide each side by '-11'.
x = -1

Simplifying
x = -1

See similar equations:

| -3=5v-5 | | Xlnx=6lnx | | x+3.5=9 | | (4f+5)-(-5f-40)=180 | | -94-x=-12x+49 | | 13x^2-16x=4 | | 4(k+5)=2(9t-2) | | 4(v-8)=-2v-26 | | 8x=-8x-7x | | xsquared+12=1 | | 2x^2=x+29 | | -7(v+4)+5(6-7v)=44 | | 5d+7x+6= | | -36-3x=64-8x | | 12-8-12= | | 5-3x/4=4 | | 66*10= | | 8x-(6x+7)=6x-47 | | ×/11=×/12-8 | | 6+8-78738+3837484849=0939v | | 5x-40=10x-50 | | 6x-7-x=17 | | 58800=P-(0.00917P) | | -12=m+1-6 | | -7x-33=-9x+25 | | x+.10=70 | | =14*2.8+21*4.2 | | 3(x-2)+5x=-2(x+3)+10x | | (5/2n=98-n | | 15y-10y-14=54.90 | | 195=-5x+5(6x+9) | | -8(-4v-8)-7v=-26+7v |

Equations solver categories